Gratis Ongkir pada Metode Pembayaran Tertentu di Shopee dalam Perspektif Hukum Islam - Mia Hanifa; Hendra Karunia Agustine; Muhammad Hasmi (Al Barakat, 2026)
Shipping free is a cost of shipment for goods borne to the buyers by the sellers during buy and sell transaction. Shopee provides the free shipping XTRA program to ease the burden on customers who are concerned about the total purchase price of goods plus the shipping costs they have to pay. Terms and conditions are applied to get free shipping, one of the criteria that shall be fulfilled by the buyer to get free shipping coupon is using a particular payment method. For customers who do not use required payment method by Shopee, this, they won’t get free shipping. This research is to learn administerial practice of free shipping only by particular payment method on Shopee platform and its relevance with Islamic legal status. The researcher used descriptive qualitative research method by using source of data earn directly from the field (field research) through the site of Shopee an interview results. The researcher carried out interview to Shopee users as sellers and buyers parties. All source data that were obtained by the researcher were re-educated, presented, and concluded in the form of narration. The result of the research are one, there were 3 things regarding of the free shipping administration was only for particular payment method; a) Shopee requires specific payment method to be eligible  for free shipping. b) There are terms and conditions other than payment methods. c) Administration fee borns to the sellers. Two, free shipping that buyers get are in accordance with the Islamic law. Shopee requires specific payment method to improve service usage of the payment method, provide security and convenient during transaction, practically it is similar with wakalah bil ujrah. Reward in the form of free shipping is earned based on the success of completing work by all criteria determined by Shopee party, in the Islamic law this practice is similar with ju’alah contract. The administration fee borns to the seller is to improve shop promise is in line with wakalah bil ujrah contract.